2018
DOI: 10.1016/j.anai.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use and effectiveness of digital health technologies in patients with asthma

Abstract: Despite the availability of proven treatment guidelines and effective therapies for asthma, poor adherence and the lack of guideline implementation remain barriers to asthma control Use of digital health technologies (DHT) is growing rapidly worldwide and is well suited to improving medication adherence and symptom control for patients with asthma A wide range of DHT were evaluated, and most were reported to have had at least some patient benefit DHT that included more interactive features or real-time feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 57 publications
1
37
0
3
Order By: Relevance
“…However, none of the reviews provide a comprehensive and current overview of the field. Some of these reviews examine a general population, including both children and adults [9,11,12], while those reviews that limit the scope to children and young people focus on particular technologies or outcomes [10,14,15]. Additionally, no reviews were found that examined how the technologies are integrated into current clinical care pathways for children and adolescents with asthma.…”
Section: Rationalementioning
confidence: 99%
See 4 more Smart Citations
“…However, none of the reviews provide a comprehensive and current overview of the field. Some of these reviews examine a general population, including both children and adults [9,11,12], while those reviews that limit the scope to children and young people focus on particular technologies or outcomes [10,14,15]. Additionally, no reviews were found that examined how the technologies are integrated into current clinical care pathways for children and adolescents with asthma.…”
Section: Rationalementioning
confidence: 99%
“…However, this review was published in 2014, and given the rapid evolution of digital technology [16], the state of the field has changed since the review was conducted; for instance, electronic inhaler monitoring is a relatively new development [17,18], with smart inhalers only recently becoming commercially available [19]. Unni et al's review [9] did analyse studies of children and adults separately, but only 16 studies concerning children were included. The review does include a wide range of outcomesadherence, health outcomes, and user perceptions -but only PubMed and EMBASE databases were searched for the study, which raises the concern that some relevant studies might have been missed [9].…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations